An evaluation of inpatient morbidity and critical care provision in Zambia. (21st November 2016) - Dart, P. J.; Kinnear, J.; Bould, M. D.; Mwansa, S. L.; Rakhda, Z.; Snell, D.
Summary: The aim of this study was to objectively measure demand for critical care services in a southern African tertiary referral centre. We carried out a point prevalence study of medical and surgical admissions over a 48‐h period at the University Teaching Hospital, Lusaka, recording the following: age; sex; diagnosis; Human Immunodeficiency Virus (HIV) status and National Early Warning Score. One‐hundred and twenty medical and surgical admissions were studied. Fifty‐four patients (45%) had objective evidence of a requirement for critical care review and potential or probable admission to an intensive care unit, according to the Royal College of Physicians (UK) guidelines. A greater than expected HIV rate was also noted; 53 of 75 tested patients (71%). When applied to the estimated 17, 496 annual acute admissions, this would equate to 7873 patients requiring critical care input annually at this hospital alone. In contrast to this demand, we identified 109 critical care beds nationally, and only eight at this institution.